Impeachment Sebagai Bentuk Pertanggungjawaban Presiden Indonesia Dalam Negara Hukum Yang Demokratis - Setiawan, Adam; Asyikin, Nehru; Hidayati, Fatma; Isnawati, Isnawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2023)
Based on the history of Indonesian state administration, there are two cases of impeachment that have occurred against active Presidents, namely President Soekarno and President Abdurrahman Wahid. However, it needs to be understood that the impeachment process is not as easy as the previous experience because it has been rigidly regulated in the 1945 Constitution of the Republic of Indonesia. The purpose of this research is to comprehensively explore the impeachment process as a form of Presidential accountability in a democratic state of law. This research is a doctrinal research, using a legislative approach and a conceptual approach. The results showed that impeachment as the President's responsibility contains two patterns, namely political and legal mechanisms. The political mechanism is when the President is demanded accountability by the DPR which is then submitted to the MPR, (a joint session between DPR and DPD) then the Constitutional Court examines, hears and decides. as for the involvement of the Constitutional Court as a form of legal mechanism. Political and legal mechanisms in the impeachment process involving the role of DPR, MPR (filled with members of DPR and DPD), and the Constitutional Court is a manifestation of the principle of checks and balances. The final result of the institution that decides the impeachment of the President and / or Vice President if proven guilty is the MPR, as a form of accountability to the people through its representatives in the MPR which contains representation of the people (DPR) and representation of groups in the region (DPD) by not also leaving the principle of the rule of law as reflected in the role of the Constitutional Court in examining, adjudicating, and deciding.